Effective and Novel Application of Hydrodynamic Voltammetry to the Study of Superoxide Radical Scavenging by Natural Phenolic Antioxidants - Stuart Belli; Miriam Rossi; Nora Molasky; Lauren Middleton; Charles Caldwell; Casey Bartow-McKenney; Michelle Duong; Jana Chiu; Elizabeth Gibbs; Allison Caldwell; Christopher Gahn; Francesco Caruso (MDPI AG, 2019)
The reactions of antioxidants with superoxide radical were studied by cyclic voltammetry (CV)—and hydrodynamic voltammetry at a rotating ring-disk electrode (RRDE). In both methods, the superoxide is generated in solution from dissolved oxygen and then measured after being allowed to react with the antioxidant being studied. Both methods detected and measured the radical scavenging but the RRDE was able to give detailed insight into the antioxidant behavior. Three flavonoids, chrysin, quercetin and eriodictyol, were studied, their scavenging activity of superoxide was assessed and the molecular structure of each flavonoid was related to its scavenging capability. From our improved and novel RRDE method, we determine the ability of these 3 antioxidants to react with superoxide radical in a more quantitative manner than the classical CV. Density Functional Theory (DFT) and single crystal X-ray diffraction data provide structural information that assists in clarifying the scavenging molecular mechanism. Hydroxyls associated with the A ring, as found in chrysin, scavenge superoxide in a different manner than those found in the B ring of flavonoids, as those in quercetin and eriodictyol.